Structural condition assessment (Wiley, 2005)
In Structural Condition Assessment, editor-in-chief Robert T. Ratay gathers together the leading people in the field to produce the first unified resource on all aspects of structural condition assessment for strength, serviceability, restoration, adaptive reuse, code compliance, and vulnerability. Organized by the four main stages of a structural evaluation, this book provides an introduction to structural deterioration and its consequences, the business and legal aspects of conducting an evaluation, initial survey and evaluation techniques for various structures, and specific tests for five of the most common structural materials (concrete, steel, masonry, timber and fabric.)